Body-focused repetitive disorders - Hossain, Rahat; Leung-Yee, Joanne; Sinyor, Mark (Canadian Medical Association journal (CMAJ), 2022)
Hossain et al present several facts about body-focused repetitive disorders. Among other things, trichotillomania and excoriation disorders involve recurrent picking that causes hair loss or skin lesions. Trichotillomania (hair pulling) and excoriation (skin picking), with repeated attempts to decrease or stop the behavior, are categorized as obsessive--compulsive and related disorders. Hair is pulled commonly from the scalp, eyebrows or eyelashes, and skin is picked from the face, arms or hands. Onset of these behaviors often coincides with puberty. They may be automatic, focused (within conscious awareness) or both. Although not formally recognized by the Diagnostic and Statistical Manual of Mental Disorders, other body-focused repetitive behaviors include nail and cheek biting.